Morbidity through 3 Years of Age in Children of Women Using Methamphetamine during Pregnancy: A National Registry Study - Gabrhelík, Roman; Skurtveit, Svetlana; Nechanská, Blanka; Mravčík, Viktor; Handal, Marte (European addiction research, 2023)
BACKGROUND: There is a lack of studies on methamphetamine (MA) exposure and morbidity in children beyond the perinatal period. OBJECTIVES: We compared morbidity in children (0-3 years) with prenatal MA exposure to opioid-exposed and to non-exposed children. METHODS: We used data from a Czech nationwide, registry-based cohort study (2000-2014). Children, who reached 3 years of age, of mothers hospitalized with (i) MA use disorder during pregnancy (MA; n = 194), (ii) opioid use disorder during pregnancy (opioids; n = 166), and (iii) general population (GP; n = 1,294,349) with no recorded history of substance use disorder (SUD). Information on inpatient contacts, length of stay, and diagnoses (International Statistical Classification of Diseases and Related Health Problems 10th Revision [ICD-10]) were assessed. Crude and adjusted odds ratios (aOR), 95% confidence interval (CI) for the risk of hospitalization, and for getting diagnosis from the ICD-10 diagnosis chapters were calculated using binary logistic regression. A stratified analysis on hospitalizations with SUD of mothers was performed. RESULTS: No significant differences were found in the measures of hospitalization between the MA and opioid groups. Children prenatally exposed to MA and opioids had higher numbers of hospitalizations and diagnoses and longer stays in hospital than children in the GP. Increased risks of certain infectious and parasitic diseases were found in both MA (aOR = 1.6; CI: 1.1-2.3) and opioid (aOR = 1.9; 1.3-2.8) groups as compared to the GP group. The most pronounced difference in stratified analysis on maternal hospitalizations related to SUD after birth was observed for injury, poisoning, and certain other consequences of external causes in the strata of the MA group who had hospitalized mothers (aOR 6.3, 1.6-24.6) compared to the strata without maternal hospitalizations (aOR 1.4, 0.9-2.3). CONCLUSION: This study suggests that children born to mothers using MA during pregnancy have similar morbidity during the first 3 years of life but higher than the GP. The excess of risk was primarily due to infections and injuries in the MA group.
Keywords: Prenatal Exposure Delayed Effects; Cohort Studies; methamfetamin; těhotenství; opioidní analgetika; ženské pohlaví; morbidita; zpožděný efekt prenatální expozice; Prenatal exposure; Methamphetamine; Long-term effects; registrace; kohortové studie; Humans; poruchy spojené s užíváním opiátů; dítě; Child; Female; Health registries; Registries; Opioid-Related Disorders; Morbidity; Hospitalization; lidé; Analgesics, Opioid; Child morbidity; Pregnancy